2017
DOI: 10.21009/jrmsi.008.2.04
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Capital Structure on Earning Per Share (Eps)

Abstract: The purposes of this research are finding the influence of Capital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They found that capital structure has a statistically insignificant relationship with EPS in all sectors except telecommunications. Saleem and Naseem (2013), Utami and Hidayah (2017) also concluded in their research that no relationship exists between the two variables. Similarly, Siddik et al, (2017) measured the relationship between capital structure and performance of banks in Bangladesh using panel data of 22 banks for the period 2005-2014.…”
Section: Findings From Europementioning
confidence: 95%
“…They found that capital structure has a statistically insignificant relationship with EPS in all sectors except telecommunications. Saleem and Naseem (2013), Utami and Hidayah (2017) also concluded in their research that no relationship exists between the two variables. Similarly, Siddik et al, (2017) measured the relationship between capital structure and performance of banks in Bangladesh using panel data of 22 banks for the period 2005-2014.…”
Section: Findings From Europementioning
confidence: 95%
“…This ratio shows the difference between capital originating from debt and from investors. The higher the ratio is, the higher the funding that comes from debt will be (Utami & Hidayah, 2017).…”
Section: Research Variablesmentioning
confidence: 99%